Effects of natural disaster on fertility rate and quality of life - Nagaratnam, Shalini (2018)
In the recent years, the frequency of disasters have increased along with greater intensity and damages. People living in disaster-prone areas respond to the disasters by adopting different strategies to improve quality of life, which includes altering their choices leading to changes in fertility rates. Fifty years ago, the fertility rates were between 5 and 6 children per woman, and now, at least half the world are below replacement rates. The intended fertility rates are decided based on the standing of their lives’ quality, where while some parents experience happiness on their newborn, some struggle to adapt to the new lifestyle. Against this background, this study intends to; (a) analyze the impact of natural disaster on fertility rates, (b) examine the impact of fertility on quality of life, and (c) investigate the international convergence in fertility. For the first and second objectives, the study employed the system Generalized Method of Moments (GMM). The first objective examines the impact of natural disasters (i.e. floods, earthquake and landslide) on fertility rates using a panel data spanning from the period 1980 to 2014 on 165 countries that faced at least one event of natural disaster, 153 countries that faced at least one event of flood, 57 countries that faced at least one event of earthquake and 32 countries that faced at least one event of landslide. Each natural disaster was measured using four measurements; the number of occurrences, the number of people killed, the number of people affected and the total damages. The analysis also included the one-period of lagged natural disaster. The findings reveal that the occurrences of natural disaster for all types of disaster decreases the fertility rates, but increases at the lagged-period. The damages and number of people affected in the floods and total disaster are positively related to the fertility rates, while the number of people killed has a negative impact on fertility rates for all disaster types. The second objective examines the impact of fertility rates on the quality of life using a panel data for 129 countries for the period 2008 to 2017. The results reveal that the relationship between fertility rates and quality of life is negative, while the square of the fertility rates had a significant and positive impact on quality of life. This results posits that quality of life and fertility rates has a ‘U’ shaped relationship. The third objective employed the convergence test using standard convergence using absolute and beta convergence, and innovative dispersion method using the relative dispersion to examine the convergence in fertility among disaster-prone countries. A total of 165 countries were analyzed between years 1975 and 2014. This study suggests countries that experience natural disasters are converging in fertility rates. The presence of convergence in fertility rates indicates that the perceived distinction between the countries is becoming less visible. Discounting the period from 1975 to 2015 when the OECD countries experienced a divergence in fertility rates, we find that the population dynamics in the OECD countries may not be different from the other sampled countries. Fertility rates in the OECD countries have declined as rapidly as the rest of the world. Dispersion in the fertility rates are also negative, indicating that the cross sectional variance in fertility rates are also becoming smaller. Although the relative dispersion showed a possible divergence, the volume of divergence is becoming smaller over the time period. This affirms that the convergence in a relative dispersion will take place in the future. Based on the findings, the study suggests that the government and policy makers place greater emphasis on the disaster preparedness and risk reduction to mitigate the effects of natural disaster on fertility rates and the quality of life. This study also recommends that the government consider taking considerable measures to improve fertility rates through education, and raising income level. In order to improve quality of life, policy measures should focus on improving social capital, institutional quality, and health sectors, which in turn would increase fertility rates.